Educação superior no Brasil: a coetaneidade entre processos de inclusão e exclusão - Luciana Goncalves de Oliveira Gotelipe (2022)
Focusing on the coexistence between the processes of inclusion and exclusion in Brazilian higher education, this work aims to expose evidence of this contradictory movement. To this end, it sought to demonstrate it through the systematization of historical series on the growth of enrolment in on-site and distance undergraduate courses, the offer of vacancies and the number of new entrants, as well as the institutions. It then presents the main government policies of national scope, inducing this process. Supported by the quantitative analysis of data from the Higher Education Census, referring to the years 2010, 2015 and 2019, and in the researched literature, it was shown that public institutions have a greater permanence of freshmen in the initial year, than the admission of students in the modality the distance has been increasing in the last ten years, but with greater exclusion. And the percentage of students who enter higher education, coming from public schools is also increasing, on the other hand, these students present greater exclusion in the initial year of entry. It was concluded that, as attested by the literature, there was a change in the Brazilian university profile, which now has a greater participation of blacks, browns, indigenous people, women and the disabled, but some differences/inequalities were maintained, or sometimes deepened, such as horizontal stratification and greater access to less prestigious institutions.